DION KHRYSOSTOMOS'UN KRALLIK SÖYLEVLERİNDE «İDEAL» KRAL TASVİRİ. - YAKUT, AYŞE (CEDRUS, 2019)
This article examines the literary portrayal of the ideal king in Dio Chrysostom's kingship orations (e βαase: or. 1-4), which were dedicated to Emperor Trajan. The orator, on the one hand, focuses on the inner qualities of a king on the level of virtues and vices. He, on the other hand, offers a specific educational programme ranging from cultural achievements in poetry, music, philosophy and oratory to basic human needs, such as nutrition and clothing. And he puts emphasis on friendship as a royal virtue. In his kingship orations, Dio Chrysostom takes an ideological approach to the Roman emperor in accordance with the standards of the Greek wisdom and aims to improve the Roman government and prevent the moral corruption of the emperor; he also mirrors Domitian's and Trajan's characters with some implicit references to their qualities. In this way, when the description of the ideal king is examined Dio's Trajanic ideology and his feelings and sentiments about the mentioned emperors are revealed.